2023
DOI: 10.3389/fsufs.2023.1097587
|View full text |Cite
|
Sign up to set email alerts
|

Multitrait Pseudomonas sp. isolated from the rhizosphere of Bergenia ciliata acts as a growth-promoting bioinoculant for plants

Abstract: Multifunctional plant growth-promoting bioinoculants are used to enhance growth, harvest yields, and add economic value to agricultural crops. In this study, such bioinoculant, BC-II-20 (Pseudomonas sp.), was isolated from the rhizospheric soil of a medicinal plant Bergenia ciliata from the Garhwal Himalayas, Uttarakhand, India. After characterization, supplementation with Pseudomonas sp. was used to study growth stimulation in a commercially important medicinal plant, Andrographis paniculata (Kalmegh), and it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Recently, it was demonstrated that plant biostimulants are very effective to ameliorate the sustainability and resilience of production systems also under stress conditions (Rouphael et al, 2022). As a matter of fact, since biostimulants are based on molecules or microorganisms that regulate plant physiology and metabolism they may promote plant growth as well as resilience against abiotic stress (Thakur et al, 2023;Di Mola et al, 2021).…”
Section: Gene Expressions Analysismentioning
confidence: 99%
“…Recently, it was demonstrated that plant biostimulants are very effective to ameliorate the sustainability and resilience of production systems also under stress conditions (Rouphael et al, 2022). As a matter of fact, since biostimulants are based on molecules or microorganisms that regulate plant physiology and metabolism they may promote plant growth as well as resilience against abiotic stress (Thakur et al, 2023;Di Mola et al, 2021).…”
Section: Gene Expressions Analysismentioning
confidence: 99%
“…PGPB is a diverse group of soil-dwelling and endophytic bacteria that inhabit the rhizosphere and endosphere of plants ( Thakur et al., 2023 ), where they form intricate interactions with their host plants and contributes to their growth and overall well-being ( Shoaib et al., 2020 ). Harnessing the full potential of PGPB involves not only identifying beneficial bacterial isolates but also their interactions within the complex microbial communities formed in the rhizosphere ( Bulgarelli et al., 2013 ; Trivedi et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…showed numerous benefits, including enhanced growth, early flowering, and increased production of photosynthetic pigments ( Thakur et al, 2023 ). Moreover, Thakur and Yadav (2023) demonstrated that AB-11, a strain of Streptomyces sp., hold promise as an agent for plant growth promotion, providing an environmentally friendly alternative to chemical fertilizers. The success of their utilisation depends on several factors, such as survival in the soil, ability to interact with the existing microbiota, genetic compatibility with the crop on which they are applied ( Cangioli et al., 2021 ), and environmental factors.…”
Section: Introductionmentioning
confidence: 99%